2009
DOI: 10.1044/1092-4388(2009/08-0111)
|View full text |Cite
|
Sign up to set email alerts
|

Objective Measures of Listening Effort: Effects of Background Noise and Noise Reduction

Abstract: Results from both dual tasks support the hypothesis that NR reduces listening effort and frees up cognitive resources for other tasks. Future hearing aid research should incorporate objective measurements of cognitive benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
466
5
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 384 publications
(518 citation statements)
references
References 28 publications
40
466
5
7
Order By: Relevance
“…Previous studies showed that NR algorithms based on spectral subtraction fail to improve speech intelligibility (e.g., Hu and Loizou 2007;Sarampalis et al 2009). However, several low-level (i.e., sensory) and high-level (e.g., linguistic) effects of NR may underlie the lack of speech perception benefits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed that NR algorithms based on spectral subtraction fail to improve speech intelligibility (e.g., Hu and Loizou 2007;Sarampalis et al 2009). However, several low-level (i.e., sensory) and high-level (e.g., linguistic) effects of NR may underlie the lack of speech perception benefits.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of this algorithm on speech perception have been investigated in previous studies (e.g., Sarampalis et al 2009). The algorithm is described in detail by Fang and Nilsson (2004).…”
Section: Noise Reduction Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Although substantial effort is required to perceive speech in extremely noisy conditions, accurate perception in moderately noisy and reverberant environments is relatively effortless (1), presumably because of the presence of general filtering mechanisms in the auditory pathway (2). These mechanisms likely influence the representation and perception of both speech and other natural sounds with similarly rich spectrotemporal structure, such as species-specific vocalizations (3)(4)(5).…”
mentioning
confidence: 99%
“…The Sentence-final Word Identification and Recall (SWIRL) test was developed for this purpose [9], inspired by [11,13]. During the test, subjects are presented with sentences in background noise individualized so 95% of all sentences are fully understood.…”
Section: Hearing Aids and Cognitionmentioning
confidence: 99%